Organ transplantation using COVID‐19‐positive deceased donors. Issue 9 (25th July 2022) - Bock, Matthew J.; Vaughn, Gabrielle R.; Chau, Peter; Berumen, Jennifer A.; Nigro, John J.; Ingulli, Elizabeth G.
Abstract : The COVID‐19 pandemic has influenced organ transplantation decision making. Opinions regarding the utilization of coronavirus disease‐2019 (COVID‐19) donors are mixed. We hypothesize that COVID‐19 infection of deceased solid organ transplant donors does not affect recipient survival. All deceased solid organ transplant donors with COVID‐19 testing results from March 15, 2020 to September 30, 2021 were identified in the OPTN database. Donors were matched to recipients and stratified by the COVID‐19 test result. Outcomes were assessed between groups. COVID‐19 test results were available for 17 694 donors; 150 were positive. A total of 269 organs were transplanted from these donors, including 187 kidneys, 57 livers, 18 hearts, 5 kidney‐pancreases, and 2 lungs. The median time from COVID‐19 testing to organ recovery was 4 days for positive and 3 days for negative donors. Of these, there were 8 graft failures (3.0%) and 5 deaths (1.9%). Survival of patients receiving grafts from COVID‐19‐positive donors is equivalent to those receiving grafts from COVID‐19‐negative donors (30‐day patient survival = 99.2% COVID‐19 positive; 98.6% COVID‐19 negative). Solid organ transplantation using deceased donors with positive COVID‐19 results does not negatively affect early patient survival, though little information regarding donor COVID‐19 organ involvement is known. While transplantation is feasible, more information regarding COVID‐19‐positive donor selection is needed. Abstract : Analysis of the OPTN database shows that early solid organ transplant outcomes using organs from COVID‐19 positive deceased donors are similar to those from COVID‐19 negative donors.